Efektivitas Pemanfaatan Zakat Produktif oleh Mustahik di Badan Amil Zakat Nasional Provinsi Sumatera Utara pada Masa Pandemi Covid-19 - Muhammad Raihan; Kamilah, K (Management of Zakat and Waqf Journal (MAZAWA), 2021)
The management of zakat has been carried out since the beginning of Islam and its development, both by individuals and groups or certain institutions. By carrying out management by formal institutions such as the National Zakat Agency (BAZNAS) it is hoped that it can increase the effectiveness of collection and allocation so that it can be used properly by the mustahik. In this study, the approach used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the utilization of productive zakat funds by mustahik in BAZNAS North Sumatra Province has not been effective. The ineffective use of productive zakat by mustahik can be seen from the ineffectiveness of the goal of productive zakat distribution by BAZNAS, namely increasing the welfare and independence of mustahik economically. Of the 15 mustahiks, only 2 of them are still operating and are able to achieve economic independence. The COVID-19 pandemic has also become an external factor that hinders mustahiks from running their business so that the capital provided cannot be fully utilized.